Implementación del sistema contable comercial en CONTABSYS variedades de la provincia de Sucumbios cantón Lago Agrio: periodo mayo-julio 2014 - Quichimbo Velitama, Yene Carmen (2016)
He present work of research called “IMPLEMENTACIÓN DEL SISTEMA CONTABLE COMERCIAL EN CONTABSYS VARIEDADES DE LA PROVINCIA DE SUCUMBIOS CANTON LAGO AGRIO: PERÍODO MAYO - JULIO DE 2014”, was developed in accordance with the rules of academic regime of the Universidad Nacional de Loja, in pursuance of a prerequisite to qualify for the degree of Engineer in Accounting and Auditing, Public Accountant Auditor To comply with the general objective: implement an accounting system in the trade will allow to know the real situation of the company, will collect documentation source to set the State of the company's initial situation; developed the initial inventory of all goods, values and obligations that has the commercial; designed documents, receipts and accounting records that support transactions made during the accounting period; the financial statements showing the real economic, financial situation of the same were drawn up. With the work provided to owner real and timely information, based on accounting and tax regulations, allowing you to comply with the requirements established by the inspection bodies, so it is recommended to continue with the accounting process applied, making use of technological tools for a more adequate control of goods through inventari system